Reinforcing Roles of Lady Health Workers in Sedayu Community Feeding Center: Six-Steps Program Planning and Evaluation - Bunga Astria Paramashanti; Sulistiyawati Sulistiyawati (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Child malnutrition remains a challenge in Indonesia's public health nutrition field. The assistance of lady health workers child feeding centers becomes important to guard nutritional issues among children in the community. To reinforce the roles of lady health workers in the community feeding center, we recruited lady health workers in two community feeding centers of Argodadi and Argorejo villages, Sedayu Subdistrict, Bantul District, in a capacity-building intervention. We were hoping that lady health workers with adequate knowledge and skills can contribute more effectively in the community-based nutrition program including nutritional status assessment and monitoring, nutrition counseling and promotion, general food supplementation, and referral system. This program was effective to increase maternal knowledge of infant and young child feeding, to improve energy and protein intakes of the children, and to add the bodyweight of the children.